FINANCIAL MODELING IN BUSINESS VALUATION - Nozimov Eldor A.; Rustamova Ruxsora Kodirovna (Ecomind Press, 2025)
This scientific article will highlight the theoretical foundations, methodology and practical application of financial modeling in the process of business valuation. The financial model is the most important analytical tool for forecasting future cash flows of a business, assessing risks and determining the value of a company. The article describes processes such as discounted cash flow (DPO), scenario analysis, sensitivity analysis, capital structure optimization on a scientific basis.
Keywords: Business valuation, financial modeling, DCF, risk analysis, cash flows, cost of capital, investment valuation, multiples, discount rate.